A Comparison of Three Different Surgical Treatments in Late Stage Kienböck's Disease - Özdemir, Ferdi; Özdeş, Hüseyin Utku; Karakaplan, Mustafa; Ergen, Emre; Aslantürk, Okan; Balıkçı Çiçek, İpek; Ertem, Kadir (Journal of Wrist Surgery, 2025)
Different treatment options exist for the late-stage Kienböck disease (KD). The functional outcomes of patients undergoing scaphocapitate fusion (SCF), tendon ball arthroplasty (TBA), and radius metaphyseal core decompression in stages 3 to 4 KD were investigated.This is a retrospective study spanning ∼11 years, conducted at our clinic, involving the operated patient KD. The study included 51 patients with an average follow-up duration of 68 months (range: 16–130 months). Patients who underwent SCF, TBA, and radius metaphyseal core decompression were divided into three groups based on the surgical approach. The range of motion of the wrist joint and grip strength of the operated wrists were assessed alongside the unaffected wrist during follow-up evaluations. Satisfaction levels among patients were measured by comparing groups internally and based on disease stages. Functional outcomes were evaluated using quick disabilities of the arm, shoulder, and hand (Q-DASH) and Mayo wrist scoring scales.Of the patients, 28 were female (54.9%) and 23 were male (45.1%). The mean age was 34 years (range: 19–62 years). There were 12 patients (23.53%) in the radial decompression group, 10 patients (19.61%) in the SCF group, and 29 patients (56.86%) in the TBA group. When the wrist joint Range of motion (ROM)s are analyzed, the losses in both stages 3A and 3B disease are significant compared with the intact wrist in all three surgical methods. When the groups were compared, a higher loss of wrist joint ROM was observed in the TBA group, especially in Kienböck stage 3B patients (p < 0.001). Furthermore, there were no differences between patient scores in stage 3A when assessments were made using Q-DASH and Mayo scores (p = 0.156 for Q-DASH and p = 0.060 for Mayo). In stage 3B, Mayo's results were similar, while the radial decompression group was reported to be more favorable in terms of Q-DASH scores (p = 0.035).KD is surgically treated with various operations identified. In terms of functional outcomes, all three surgeries are considered satisfactory. However, in young and active patients, even in advanced stages of the disease, metaphyseal core decompression should be attempted as an initial treatment due to its easier approach and the avoidance of direct manipulation of the carpus.
Keywords: Kienböck disease; radial decompression; scaphocapitate fusion; tendon ball